An action research project on the effectiveness of using authentic materials on the Internet to improve 12th form students' extensive reading at B Phu Ly High School - Nguyễn, Thị Thúy Vân (ĐHNN, 2017)
Extensive reading is believed to develop good reading habits, to build up knowledge of vocabulary and structures, and to encourage a liking for reading. Materials for extensive reading are available everywhere but Internet-based materials seem to be the most suitable for high school students because the World Wide Web now is easily accessible with an endless supply of authentic materials in the target language where students can start on their own.